Tour Recommendation System Based On User Interest and Surrounding Facilities in North Sumatera Using Simple Multi-Attribute Rating Technique With Dijkstra's Algorithm - Muthoharoh, Luluk; Ahmad Luky Ramdani; Ira Safitri; Muhammad Dhoni Apriyadi (EKSAKTA: Journal of Sciences and Data Analysis, 2025)
In this study, we collected data on tourist attractions, tourist attractions utilities, on the island of Sumatra, especially in Toba and Samosir districts in North Sumatra Province. In this process, information was collected on 100 tourist destinations with the highest popularity based on Google Maps Review. To determine the interest of tourists, the SMART method is used to obtain the value of tourist interest in each tourist spot based on the weight determined on each criterion. Meanwhile, entropy is used to determine the value of facilities available at tourist attractions. The value represents the interest of tourists and the facilities available around the tourist attractions. The results of this research show that in the aspect of running time Dijkstra's algorithm is fast algorithms